2018
DOI: 10.1093/ndt/gfy167
|View full text |Cite
|
Sign up to set email alerts
|

The impact of symptoms on health-related quality of life in elderly pre-dialysis patients: effect and importance in the EQUAL study

Abstract: In elderly CKD Stage 4/5 patients, symptoms have a substantial impact on QoL. This indicates symptoms should have a more prominent role in clinical decision-making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
28
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 31 publications
5
28
1
1
Order By: Relevance
“…45 Moreover, a higher symptom burden has also been associated to a lower quality of life. 2 In our present study, we found that both constipation and decreased appetite were risk factors for decline in nutritional status. Constipation is prevalent in older adults and has previously been reported to be associated with poor appetite and nausea, factors that affect the energy and nutrient intake.…”
Section: Discussionsupporting
confidence: 50%
See 1 more Smart Citation
“…45 Moreover, a higher symptom burden has also been associated to a lower quality of life. 2 In our present study, we found that both constipation and decreased appetite were risk factors for decline in nutritional status. Constipation is prevalent in older adults and has previously been reported to be associated with poor appetite and nausea, factors that affect the energy and nutrient intake.…”
Section: Discussionsupporting
confidence: 50%
“…O LDER ADULTS WITH advanced chronic kidney disease (CKD) form a high-risk group for poor nutritional status and high overall disease burden. 1,2 The prevalence of protein-energy wasting (PEW) in this vulnerable population is high, and increases with age. 3 Patients who undergo maintenance dialysis have a significant decline in nutritional parameters, and those diagnosed with PEW have a higher risk of mortality and hospitalizations.…”
Section: Introductionmentioning
confidence: 99%
“…Patients with advanced chronic kidney disease (CKD) have shown to be more vulnerable to mental health problems, such as anxiety and depression [10]. In this population, emotional symptoms, like symptoms of anxiety and depression, worrying, sleep disorders, perceived lack of social support, and reduced social interactions, affect not only health-related quality of life (HRQoL) [11][12][13][14], but have also been associated with adverse clinical outcomes and increased mortality risk [15,16]. Above and beyond, the presence of CKD is an important risk factor for a more severe course of COVID-19, as patients with advanced CKD (stage G4/G5; severely decreased glomerular filtration rate or kidney failure) have a 2.5 times increased mortality risk, compared to those with normal kidney function [1].…”
Section: Introductionmentioning
confidence: 99%
“…Impaired HRQoL is well described among patients with chronic kidney disease (CKD) and found to correlate with factors such as symptom burden [ 9 ], hypertension, anemia, nutritional status, dialysis modality, depression, cognitive dysfunction and frailty [ 10–14 ], and also education, depression, exercise habits [ 15 ], proteinuria [ 16 ] and inflammatory status [ 17 ]. Low HRQoL scores in dialysis patients have proved to be strong and independent predictors of hospitalization and mortality [ 18–20 ].…”
Section: Introductionmentioning
confidence: 99%